2018
DOI: 10.1038/s41598-018-31294-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of putative chemoreception genes from Cyrtorhinus lividipennis (Hemiptera: Miridae) antennal transcriptome

Abstract: Cyrtorhinus lividipennis Reuter (Hemiptera: Miridae) is an important egg predator of planthoppers which are destructive rice pests. The chemosensory genes in the mirid antennae play important roles in mating and prey-seeking behaviors. To gain a better understanding of the olfaction of C. lividipennis, we sequenced the antennal transcriptomes of the predator to identify the key olfaction genes. We identified 18 odorant binding proteins (OBPs), 12 chemosensory proteins (CSPs), 1 Niemann-Pick C2 protein (NPC2), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 72 publications
0
21
0
Order By: Relevance
“…Previous studies have demonstrated sex-based differences in the chemosensory genes of insects, such as Tessaratoma papillosa (Wu et al, 2017), C. lividipennis (Wang et al, 2018), and A. lucorum (Ji et al, 2013). In insects, the perception of chemical cues, including sex pheromones and plant volatiles, is important to find a conspecific partner and food sources, respectively (Yang et al, 2016;Chang et al, 2017;Wang et al, 2018). In our study, sexual differences were determined in 29 chemosensory genes of A. chinensis, with AchiGR1, AchiGR2, and AchiOBP28 expressed at higher levels in the antennae of females than males regardless of whether the insects were full or hungry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated sex-based differences in the chemosensory genes of insects, such as Tessaratoma papillosa (Wu et al, 2017), C. lividipennis (Wang et al, 2018), and A. lucorum (Ji et al, 2013). In insects, the perception of chemical cues, including sex pheromones and plant volatiles, is important to find a conspecific partner and food sources, respectively (Yang et al, 2016;Chang et al, 2017;Wang et al, 2018). In our study, sexual differences were determined in 29 chemosensory genes of A. chinensis, with AchiGR1, AchiGR2, and AchiOBP28 expressed at higher levels in the antennae of females than males regardless of whether the insects were full or hungry.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, sexual differences were determined in 29 chemosensory genes of A. chinensis , with AchiGR1 , AchiGR2 , and AchiOBP28 expressed at higher levels in the antennae of females than males regardless of whether the insects were full or hungry. The higher-level expression of AchiOBP13 and AchiOBP16 only in full female A. chinensis suggests that these genes encode proteins related to oviposition selection behavior ( Pelosi et al, 2006 ; Wu et al, 2017 ; Wang et al, 2018 ). AchiGRs ( 1 and 2 ), AchiIR6 , and AchiOBPs ( 6–8 , 12 , 20–22 , 28 , and 34 ) were predominantly expressed in full male A. chinensis and may thus be involved in mate searching ( Liu et al, 2012 ; Gu et al, 2014 ; Wang et al, 2018 ) or the recognition of pheromone molecules ( Liu et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…C. lividipennis was microinjected with dsRNA as described by Wang et al (2018). In a preliminary study, we evaluated five different dsRNA concentrations, which were designated high (80 and 100 ng), medium (40 and 60 ng), and low (20 ng); 60 ng dsFz2 was selected as an optimum concentration based on the survival rate and RNAi efficiency of C. lividipennis (data not shown).…”
Section: Synthesis Of Dsrna and Microinjectionmentioning
confidence: 99%